A Quantative Framework Model for Analyzing the Actuarial Portfolio Risks At the Saudi Market for Cooperative Insurance By Using the Non-parametric Regression - Soliman, Yasser (The Arab Journal of Administration, 2019)
This research addresses the identification of technical and financial indicators that affect the insurance motion net or failure for every cooperative insurance section inside the Kingdom of Saudi Arabia. These factors have been identified in six independent variables. A quantative model is being used in this study based on the non-parametric regression. This study aims at improving the efficiency of technical operations at the Saudi Market for cooperative insurance in order to push up the insurance market inside the Kingdom and especially within the rapid growth rate, which has been accomplished by the insurance sector inside the Kingdom. This is added to the socio-economic role that the insurance sector plays. Yet, a serious insufficiency has been observed within the technical operations for most of the insurance sections inside the Kingdom represented in a direct proportion between loss rates and retention. In addition to that, there is a low excess in the insurance motion for most of the insurance sections and a failure made by certain branches at the insurance motion nucleus. This study also shows the importance of using and activating recent quantative mathematical methods for improving the efficiency of the insurance technical and operations efficiency in general and the special technical operations for insurance restoration. This would represent the very direct reflections on the nucleus of the insurance sector. The study aims to propose a quantitative model to predict the quality of the technical operations of the insurance sector by using the non-parametric regression, As well as the mechanism of the proposed model, represented in the face of rapid changes in the market, and the internal and external competition, which works to reduce errors contrast, The proposed model classifies insurance sectors and companies according to the quality of insurance and re-insurance activity.